2018
DOI: 10.1007/s10067-018-4314-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic lung disease in U.S. Veterans with rheumatoid arthritis and the impact on survival

Abstract: Introduction/Objectives: Assess the impact of chronic lung diseases (CLD) on survival in rheumatoid arthritis (RA). Method: Among participants in the Veterans Affairs Rheumatoid Arthritis (VARA) Registry, a prospective cohort of U.S. Veterans with RA, we identified CLD and cardiovascular disease (CVD) using administrative and registry data. Demographics, smoking status, RA characteristics including Disease Activity Score in 28 joints (DAS28), and disease-modifying anti-rheumatic drug (DMARD) use were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Such delays are likely to worsen RA outcomes by unnecessarily denying patients the anchor csDMARD for this disease. Reassurance of the benign effect of MTX on established RA-ILD comes from no association found between MTX and hospitalised severe ILD episodes in USA National Databank for Rheumatic Diseases27 and mortality from ILD in the USA Veterans Affairs Rheumatoid Arthritis Registry 28. Furthermore, a retrospective analysis of prognostic factors in 78 cases of RA-ILD, where MTX was specifically used as a therapeutic agent in 67%, found this to be strongly associated with survival 29…”
Section: Discussionmentioning
confidence: 99%
“…Such delays are likely to worsen RA outcomes by unnecessarily denying patients the anchor csDMARD for this disease. Reassurance of the benign effect of MTX on established RA-ILD comes from no association found between MTX and hospitalised severe ILD episodes in USA National Databank for Rheumatic Diseases27 and mortality from ILD in the USA Veterans Affairs Rheumatoid Arthritis Registry 28. Furthermore, a retrospective analysis of prognostic factors in 78 cases of RA-ILD, where MTX was specifically used as a therapeutic agent in 67%, found this to be strongly associated with survival 29…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, respiratory failure is mostly caused by inflammation [30] and increased oxidative stress [31]. Biologics may be significantly associated with lung disease in RA patients [32][33][34]. Another review article mentioned that MTX, LEF, TNFi, RTX, and TCZ may cause pneumonitis [35], which was not demonstrated in our current study and warrants further investigation.…”
Section: Discussionmentioning
confidence: 55%
“…Our study highlights RA as a vulnerable population related to this important patient-reported outcome(7). A recent study of mostly men in the Veteran Affairs RA registry showed that chronic lung disease was associated with increased mortality(16) further underscoring the importance of understanding the effect of respiratory factors on health for patients with RA. In the analysis comparing subjects with prevalent clinically significant dyspnea on exertion to those without, subjects with clinically significant dyspnea on exertion had high rates of smoking, sedentary activity, poor functional status, excess comorbidities, and more severe RA.…”
Section: Discussionmentioning
confidence: 99%